Cinema and pedagogy: reflections on teacher training - Osorio, Angélica del Pilar; Rodríguez, Víctor Manuel (Universidad Pedagógica y Tecnológica de Colombia, 2010)
This article forms part of a research process undertaken in the framework of the project Cinema as an opportunity for reflection in the pedagogical field: a look at teacher training. In this project, we consider the place of film in contemporary society and its relationship to pedagogy and teacher training, proposing training as experience, and not as a continuum disconnected from the subjects who live it. Based on this, we construct considerations about film, pedagogy and power in the context of the society of spectacle, and then address the relationship between training, film, and pedagogy, where ‘experience’ and ‘film reading’ become articulating concepts for critical reflection about innovative practices in education.